Leadership Strategy of Madrasah Principals in an Effort to Realize an Excellent Madrasah at MAN 1 North Kolaka - Firdaus Kuddus; Misykat Malik Ibrahim; St. Syamsudduha (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to determine: (1) what leadership strategies are implemented by madrasah principals in realizing superior madrasahs, (2) what is the role of madrasah principals in implementing strategies in realizing superior madrasahs, and (3) how teachers and staff are involved in implementing the madrasah principals' leadership strategies in realizing superior madrasahs. The results of the study indicate that madrasah principals implement vision and mission-based planning strategies that are aligned with the needs of the madrasah, participatory implementation through empowerment of teachers and education staff, and continuous evaluation through academic supervision and regular evaluation meetings. This strategy focuses on improving the quality of education, fostering student character, optimizing human resources, and strengthening collaboration with all madrasah members. Madrasah principals implement three main strategies, namely: (1) strengthening religious moderation through religious activities, habituating Yaumiyah worship, tadarus, and short-term Islamic boarding schools; (2) improving the quality of learning by implementing innovative curricula, digital learning (e-learning), and collaboration between teachers; and (3) developing educational facilities and infrastructure such as laboratories, libraries, internet networks, and public facilities that support a conducive learning environment. These three strategies are implemented in an integrated manner through visionary, participatory leadership, and are oriented towards improving the quality of madrasahs.